The common NOD2/CARD15 variant P268S in patients with non-infectious uveitis: a cohort study. Issue 1 (December 2015) - Marrani, E.; Cimaz, R.; Lucherini, O; Caputo, R.; Vitale, A.; Cantarini, L.; Simonini, G.
Abstract Background The etiology of Autoimmune chronic uveitis (ACU) is still unknown; NOD2/CARD15 gene mutations are responsible for the Blau Syndrome and can induce uveitis in animal models. Presentation of the hypothesis Aim of our study was to assess if NOD2/CARD15 variants have a role in the etiology or in the clinical course of patients with ACU, either idiopathic or associated with other inflammatory diseases. Testing the hypothesis We consecutively enrolled 25 patients (19 pediatric and 6 adults) affected with ACU. For each patient medical history was reviewed and clinical data were recorded. Allelic and genotypic frequencies of NOD2/CARD15 variations were calculated in patients and matched with those of 25 healthy controls. The statistical analysis was performed. Fifteen patients showed the polymorphism P268S/SNP5 (SNP rs2066842) as heterozygous carriers while two patients were homozygous for the same polymorphism; one patient carried also the variant c647 18–16 TCT on intron 3, not previously reported in the literature. Statistical analysis for NOD2/CARD15 genotyping showed significant differences between patients and controls for allelic frequencies (p  = 0.04, OR: 4.03, 95 %; CI = 1.2–13.5) but not for genotypic frequencies. We could not identify a significant phenotype-genotype correlation. Implications of the hypothesis In our cohort of Italian patients, the NOD2/CARD15 common variant P268S/SNP5 could potentially be significantly associated with ACU.